1996
DOI: 10.1002/(sici)1099-1573(199612)10:8<694::aid-ptr923>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Constituents Isolated fromLychnophora salicifolia (Asteraceae)

Abstract: Lychnophora salicifolia (Asteraceae), a native Brazilian medicinal plant used in folk medicine against some diseases, revealed the presence of two known caryophyllene derivatives, in a satisfactory yield: lychnopholic acid 1 and acetyl lychnopholic acid 2. These compounds exhibited antifungal activity by the agar diffusion method, and antibacterial activity by the methods of diffusion and minimum inhibitory concentration (MIC). However, compound 2 was more potent than 1, suggesting that the acetyl group is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
1
7
0
5
Order By: Relevance
“…Comparison with the fragmentation profiles of chlorogenic acids described in the literature supported our identification of this type of compound [25][26][27][28]. As for the other compounds present in the evaluated extract, accurate mass data and comparison with previously described standards isolated by our research group were essential for their complete structural elucidation [3,4,12,[29][30][31] (for complete details and access to the original spectra, see supplementary material).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Comparison with the fragmentation profiles of chlorogenic acids described in the literature supported our identification of this type of compound [25][26][27][28]. As for the other compounds present in the evaluated extract, accurate mass data and comparison with previously described standards isolated by our research group were essential for their complete structural elucidation [3,4,12,[29][30][31] (for complete details and access to the original spectra, see supplementary material).…”
Section: Resultssupporting
confidence: 70%
“…It is considered to be the most typical [1] and the most polymorphic [2] species of the genus. Its antibacterial activity against Staphylococcus aureus and its antifungal properties, including its action against Candida albicans [3], have been reported. The extracts from its leaves and flowers have been described to display trypanocidal action [4].…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies involving pharmacological activities with these species revealed the importance of two compounds: the flavonoid vicenin-2 (VIC) with anti-inflammatory and also anticancer activities, and the lychnopholic acid (LA) with antibacterial and trypanocidal activities as well. [2][3][4][5] These compounds are present in large amounts in hydroalcoholic extract from leaves of Lychnophora salicifolia and are present in most studied populations of this plant. 6 VIC and LA structures are illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids isolated from the ethanol extracts of the leaves and stems of L. affi nis, demonstrated activity in cell cultures of human nasopharyngeal carcinoma (9KB) (Le Quesne et al, 1976), as well as the sesquiterpene lactones isolated from L. trichocarpha presented antitumor activity against several type cells (Saúde, 1994). Acetyl lychnopholic acid isolated from the ethanol extract of L. salicifolia leaves and stems (Miguel et al, 1996) and the sesquiterpenes from L. trichocarpha presented antimicrobial activity (100μg/mL) (Saúde et al, 2002). Lychnophora pinaster Mart, commonly known as "arnica", "arnica-da-serra" or "candeia" is used in infusions, in baths, or macerated in "cachaça" (sugarcane spirit) or ethanol as anti-fl ogistic, anti-rheumatic, and analgesic.…”
Section: Introductionmentioning
confidence: 68%